2015
DOI: 10.1093/cvr/cvv205
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for cardiovascular disease: advances in vector development, targeting, and delivery for clinical translation

Abstract: Gene therapy is a promising modality for the treatment of inherited and acquired cardiovascular diseases. The identification of the molecular pathways involved in the pathophysiology of heart failure and other associated cardiac diseases led to encouraging preclinical gene therapy studies in small and large animal models. However, the initial clinical results yielded only modest or no improvement in clinical endpoints. The presence of neutralizing antibodies and cellular immune responses directed against the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 176 publications
(185 reference statements)
2
95
0
Order By: Relevance
“…23 Most therapeutic applications of miRNA require packaging the nucleic acid in a vector or nanovehicle, example of which include adenovirus (AV), adeno-associated virus (AAV), liposomes, polycationic polymers, and organic/ inorganic nanoparticles. [24][25][26][27][28][29] Kota et al, for example, showed that miR-26a, a downregulated miRNA in hepatocellular carcinoma, could be delivered to liver cancer cells using AAV where it induced tumor-specific apoptosis in a mouse model of liver cancer. 30 Moreover, our group developed a poly(lactic-coglycolic acid)/polyetherimide/hyaluronan (PLGA/PEI/HA)-based vehicle as a carrier of miR-145 and further showed that PLGA/PEI/HA/miRNA complexes were delivered efficiently to tumor cells within colon carcinoma xenografts in mice where they exhibited significant antitumor effects.…”
mentioning
confidence: 99%
“…23 Most therapeutic applications of miRNA require packaging the nucleic acid in a vector or nanovehicle, example of which include adenovirus (AV), adeno-associated virus (AAV), liposomes, polycationic polymers, and organic/ inorganic nanoparticles. [24][25][26][27][28][29] Kota et al, for example, showed that miR-26a, a downregulated miRNA in hepatocellular carcinoma, could be delivered to liver cancer cells using AAV where it induced tumor-specific apoptosis in a mouse model of liver cancer. 30 Moreover, our group developed a poly(lactic-coglycolic acid)/polyetherimide/hyaluronan (PLGA/PEI/HA)-based vehicle as a carrier of miR-145 and further showed that PLGA/PEI/HA/miRNA complexes were delivered efficiently to tumor cells within colon carcinoma xenografts in mice where they exhibited significant antitumor effects.…”
mentioning
confidence: 99%
“…Cells were viewed by fluorescence microscopy at different time points after transfection (24,48, and 72 h), and imaged based on fluorescein isothiocyanate (FITC) channels. Finally, the cells were harvested after being transfected for 72 h, and the total RNA was extracted with Trizol according to the manufacturer's instruction.…”
Section: Gene Transfer and Mir-26a Expression Assaymentioning
confidence: 99%
“…Among the several angiogenic factors studied, the initial gene therapy trials evaluated the effect of angiopoietins, FGF, HIF-α, and VEGF-A in the treatment of either ischemia-induced vascular conditions or peripheral occlusive disorders. 40 The VEGF family of growth factors is crucial in regulating several endothelial functions including vasodilation and nitric oxide release, recruitment of circulating progenitor cells, regulation of vascular permeability, and endothelial proliferation and migration, 41 making it particularly well-suited for gene therapy targeting endothelial dysfunction.…”
Section: Dna-based Therapeuticsmentioning
confidence: 99%
“…40 An example of DNA-based gene therapy using proangiogenic VEGF is the ongoing KAT301 clinical trial. 40 This trial is evaluating the safety and efficacy of the adenoviral vector-mediated delivery of VEGF-D, a mature form of VEGF, delivered using the NO-GA-mediated transendocardial injection system in patients with severe coronary heart disease (NOGA® XP Cardiac Navigation System, Biologics Delivery Systems Group, Cordis Corporation, Miami Lakes, FL). 42 Preliminary results at 3 months demonstrated increased myocardial perfusion with intramyocardial delivery of VEGF-D in segments with the lowest perfusion reserve, thus justifying a phase II/III evaluation.…”
Section: Dna-based Therapeuticsmentioning
confidence: 99%